The reality of the application of strategic planning for human resources and their role in strategic success: an analytical study of the views of Managers for higer school in private and international schools in the city of Erbil - Ronyaz Hayyas Mahmood; Mudhafar Hamad Ali; Shirin Jamal Mohammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The purpose of research is to explain the reality of strategic planning for human resources, its dimensions (vision and strategic philosophy of human resources, human resource planning), And its role in strategic success, its dimensions (survival, adaptation, growth). As well as identifying the nature of the relationship and the impact between the strategic planning of human resources and strategic success. In the light of the objectives for research, the problem of the study was summarized in several questions, which is the extent to which principals of private and international preparatory schools practice strategic planning for human resources in the city of Erbil, and what is the nature of the relationship and the impact between strategic planning for human resources on strategic success. The researchers relied on the descriptive analytical approach. To describe the main and sub-variables, as well as to analyze the relationships and impact between the two research variables, the research community represented the number of private middle school principals in Erbil is (39), The number of principals in international preparatory schools reached (31). Then Distribute (70) Questionnaire, (67) questionnaires were retrieved and (67) of them were valid for analysis. Hypotheses were tested by applying statistical methods by the computer program (SPSS V.25). The research reached a set of main conclusions, including the results of correlation analysis revealing the existence of positive and high-level significant relationships between strategic planning for human resources and strategic success at the macro and micro levels. In addition, there is a positive impact and significant levels of the independent variable (strategic planning for human resources) on the dependent variable (strategic success), According to what the analysis indicators have produced at the macro and partial levels. The research also suggested focusing on the principal of the surveyed schools in adapting to changes in the external environment, in order to gain a competitive advantage with competing schools and try to keep up with that competition and overcome them.